TRANSLATION IS IMPOSSIBLE: A COMPARATIVE STUDY OF IDEOLOGICAL MEANING OF “THE BEATITUDES” IN MATHEW CHAPTER 5 OF KUPANG MALAY, INDONESIAN, AND ENGLISH BIBLE - Yandres Answo Djedelbert Lao (Postgraduate School, Universitas Nusa Cendana, 2018)
This study entitled TRANSLATION IS IMPOSSIBLE: A COMPARATIVE STUDY OF IDEOLOGICAL MEANING OF “THE BEATITUDES” IN MATHEW CHAPTER 5 OF KUPANG MALAY, INDONESIAN, AND ENGLISH BIBLE. It aims at; 1) figuring out types of ideological meaning of “The Beatitude” in Kupang Malay, Indonesian, and English Bible; and 2) finding out the differences of ideological meaning of “The Beatitude” of Kupang Malay, Indonesian, and English Bible that contribute to the religious meaning. The data of this research were taken from Mathew chapter 5 verses 1 to 12 of Kupang Malay, Indonesian, and English Bible. Comparative analysis was applied in investigating this topic. The result of this research proved that there are three types of ideological meaning found in three different languages of Bible. “The Beatitudes” in Indonesian and English Bible are equivalent in form of ideology of understanding real life circumstance while Kupang Malay version has ideology as subject determination and social status types. The dissimilarities were found on the construction of paradox, sources, and the use background of the ideological features of those three different languages of Bible. The final finding of this project confirms that translation is impossible in terms of ideological meanings used in “The Beatitudes” found in Kupang Malay, Indonesian, and English Bible.